2011
DOI: 10.2478/v10014-011-0025-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of longevity in Slovenian holstein cattle

Abstract: Analysis of longevity in Slovenian holstein cattle The longevity of Slovenian Holstein population was analysed using survival analysis with a Weibull proportional hazard model. Data spanned the period between January 1991 and January 2010 for 116,200 cows from 3,891 herds. Longevity was described as the length of productive life-from first calving till culling or censoring. Records above the sixth lactation were censored to partially avoid preferential treatment. Statistical model included the effect of age at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 13 publications
3
12
0
Order By: Relevance
“…Strapakova et al (2014) stated that the subsequent risk ratio increased moderately at the end of the first parity and that the trend of culling risk was similar across and along each parity. Potocnik et al (2011) reported that risk level at the end of parity can increase significantly 271 days after the start of milking and during dry periods, which is in agreement with our findings. Vukasinovic (2001) found that cows in the first parity were more vulnerable to culling than those at parity four and also increased gradually after that point, which indicated different selection criteria in the first parity; culling risk also increased after this parity.…”
Section: Interaction Between Parity × Stage Of Lactation and Proportisupporting
confidence: 83%
“…Strapakova et al (2014) stated that the subsequent risk ratio increased moderately at the end of the first parity and that the trend of culling risk was similar across and along each parity. Potocnik et al (2011) reported that risk level at the end of parity can increase significantly 271 days after the start of milking and during dry periods, which is in agreement with our findings. Vukasinovic (2001) found that cows in the first parity were more vulnerable to culling than those at parity four and also increased gradually after that point, which indicated different selection criteria in the first parity; culling risk also increased after this parity.…”
Section: Interaction Between Parity × Stage Of Lactation and Proportisupporting
confidence: 83%
“…These results are similar to those observed by Zavadilová and Stípková (2012), who reported a genetic correlation between rump width and Long2 of -0.15, and less than that observed by Cruickshank et al (2002) and Zavadilová and Stípková (2012), who found correlations between rump width and Long5 of -0.27 and Long4 of -0.29, in Jersey and Holstein cows, respectively. Rump traits are associated with calving ease, this being important for the dairy industry, where cows with calving problems are less profitable due to the increase in veterinary costs and The average for Long2 (2.66) ( Table 3) was similar to that observed in dairy cows in the United States of America by Tsuruta et al (2005), with an average of 2.8 initiated lactations, slightly lower than those reported by Potočnik et al (2011) in Slovenia and Strapák et al (2011) in Slovakia, with averages of 3.0 and 3.4 lactations initiated, respectively, for Holsteins and Simmental dairy cows.…”
Section: Resultsmentioning
confidence: 71%
“…Longevity genetic evaluation for the Brown dairy cattle population in Slovenia was first implemented by Potočnik et al (2011). Breeding values were estimated using a unique baseline hazard for the whole period considered.…”
Section: Introductionmentioning
confidence: 99%